Peranan Media Power Point Interaktif Berbasis Multimedia Dalam Mendampingi Belajar Siswa Di Kelas III (Tiga) Sekolah Dasar Pada Pembelajaran Bahasa Inggris: Parts of Tree - Dhea Meliani; Herlina Purba; Lilik Musyiarti (Program Studi PGSD Kampus UPI di Serang, 2021)
English is a compulsory subject at all levels of education, including elementary school. However, this subject is often considered difficult by students and less desirable. This is because they do not master the vocabulary and rarely practice it in everyday life. Whereas mastery of vocabulary itself is a fundamental thing in order to master English. Lack of vocabulary mastery can be caused by several factors including the way the vocabulary is delivered in its own way in learning. In overcoming these problems, the teacher's role is very important in conveying learning to be more conveyed to students. In the current era of technology, there are many things that can be done especially for education in schools. The role of digital-based interactive power point media can be used as an educational tool to deliver teaching materials that are simple, interesting, and not monotonous. This is done with the aim that learning becomes more interactive, not boring and makes the learning process more meaningful. This research approach uses a qualitative approach, while the methodology uses content analysis/content analysis, regarding an in-depth discussion of a topic which is then described. Data collection techniques used in this study are data reduction, data presentation, conclusions and verification. The results show that the application of interactive multimedia in learning English vocabulary begins with planning activities such as making lesson plans and making interactive multimedia in the form of power points. In the process, the teacher asks students to actively pay attention to the slides that have been displayed. The main material focused on class (III) students is Parts of Tree. After that, enter the evaluation activity, where the teacher displays a slide in the form of a question and then the students are appointed to understand the meaning of the question and answer the question itself.